How an Opportunistic Infection Can Mess with Your Brain and Take Your Breath Away: A Rare Case of Simultaneous Lung and Brain Abscess due to Streptococcus anginosus. (1st April 2015) - Al-Saffar, Farah; Torres-Miranda, Daisy; Ibrahim, Saif; Shujaat, Adil
Abstract : Streptococcus anginosus ( S. anginosus ) is considered a friendly bug and is a one of many different bacteria that constitute the normal flora of the oral cavity. Nevertheless, it has been infrequently associated with more invasive infections, like lung abscess. It is extremely rare to have multisystemic involvement with S. anginosus group. We present a unique case of pulmonary and brain abscess due to S. anginosus in an immunocompetent patient.